(untitled) (Bioscience Journal, 2015)
The use of DNA sequences analysis has been an important mean to distinguish and to identify populations of organisms at different levels. By molecular markers several complex organisms have been successful detected in plants for distinct aims. Ribosomal DNA (rDNA) has been used to evaluate genetic variability, microorganism phylogeny and to develop specific primers for detection of plant pathogens in plant tissues. In this study, the objective was to characterize isolates of Colletotrichum gossypii var. cephalosporioides and Colletotrichum gossypii, collected in different regions of Brazil, by analyzing the nucleotide sequence of rDNA regions. ITS1, ITS2, and the intervening 5.8S gene were amplified by PCR and their sequences compared to each other and to those from other species registered in the GenBank. The rDNA of isolates associated with Gossypium spp. showed sequence identities ranging from 96 to 100% in the ITS1 region, 98 to 100% in the 5.8S gene, and 97 to 100% in the ITS2 region. The sequences were submitted to UPGMA analysis, and according to the phylogenetic trees, the C. gossypii var. cephalosporioides and C. gossypii species clustered together along with isolates of Glomerella cingulata from mango and papaya, and thus no distinction could be made between isolates of those organisms.